Argentina's recovery and excess capital shallowing of the 1990s - Kydland, Finn; Zarazaga, Carlos (Estudios de Economía, 2016)
The paper examines Argentina’s economic expansion in the 1990s through the lens of a very parsimonious neoclassical growth model. The main finding is that investment remained considerably weaker than what the model would have predicted. The resulting excessive “capital shallowing” could be identified as a weakness of the rapid economic growth of the 1990s that may have played a role in Argentina’s ultimate inability to escape the crisis that started to unfold towards the end of that decade.